Citra Perusahaan Traveloka Terhadap Kepuasan dan Loyalitas Pelanggan - Nada Nabigha Adria; Niken Febrina Ernungtyas (Jayapangus Press, 2020)
This article discusses the impact of company image, customer satisfaction on customer loyalty in travel agents. A corporate image model, customer satisfaction. customer loyalty is developed and tested. Direct and indirect relationship between three variables. The key implication for travel agents is to build strong emotional ties with customers and enhance the company's image through trust and service delivery. Therefore, understanding is very important to examine, this research aims to understand how the company's image potential in increasing customer satisfaction and loyalty. This study uses a quantitative method by distributing questionnaires to 76 respondents. Data processing is done by ssps. The results of the study show that company image and customer satisfaction can increase customer loyalty.